YinChen WuLing powder attenuates non-alcoholic steatohepatitis through the inhibition of the SHP2/PI3K/NLRP3 pathway - Yuan, Xingxing; Yang, Liuxin; Gao, Tinting; Gao, Jiawei; Wang, Bingyu; Liu, Chengxiang; Yuan, Wei (Frontiers in Pharmacology, 2024)
Background: YinChen WuLing Powder (YCWLP) has been recommended by consensus for the treatment of non-alcoholic steatohepatitis (NASH); nevertheless, its specific pharmacological mechanisms remain to be elucidated. This study aims to dissect the mechanisms underlying the therapeutic effects of YCWLP on NASH using a hybrid approach that encompasses network pharmacology, molecular docking, and in vitro experimental validation.We compiled the chemical constituents of YCWLP from the Traditional Chinese Medicine System Pharmacological Database and Analysis Platform (TCMSP), while potential targets were predicted using the SwissTargetPrediction database. To identify NASH-related candidate targets, comprehensive retrieval was carried out using five authoritative databases.Protein-Protein Interaction (PPI) networks of direct targets of YCWLP in NASH treatment were then constructed using the String database, and functional enrichment analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway, were conducted through the Database for Annotation, Visualization, and Integrated Discovery (DAVID) database.Core targets were discerned using the Molecular Complex Detection (MCODE) and cytoHubba algorithms. Subsequently, molecular docking of key compounds to core targets was conducted using AutoDock software. Moreover, we established a free fatty acid-induced HepG2 cell model to simulate NASH in vitro, with YCWLP medicated serum intervention employed to corroborate the network pharmacology-derived hypotheses.The network pharmacology analysis furnished a list of 54 compounds from YCWLP and 167 intersecting targets associated with NASH. Through analytic integration with multiple algorithms, PTPN11 (also known as SHP2) emerged as a core target of YCWLP in mitigating NASH. Our research reveals that YCWLP exerts therapeutic effects against NASH by inhibiting lipid accumulation and inflammation, which involves the attenuation of pyroptosis via the SHP2/PI3K/NLRP3 pathway.